2014 22nd International Conference on Pattern Recognition 2014
DOI: 10.1109/icpr.2014.199
|View full text |Cite
|
Sign up to set email alerts
|

Forest Species Recognition Using Deep Convolutional Neural Networks

Abstract: Forest species recognition has been traditionally addressed as a texture classification problem, and explored using standard texture methods such as Local Binary Patterns (LBP), Local Phase Quantization (LPQ) and Gabor Filters. Deep learning techniques have been a recent focus of research for classification problems, with state-of-the art results for object recognition and other tasks, but are not yet widely used for texture problems. This paper investigates the usage of deep learning techniques, in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 12 publications
2
59
2
3
Order By: Relevance
“…We cannot compare to AlexNet as it requires input images of size 227x227. Our method outperforms the state of the art [8] on the Macroscopic forest species dataset (+1.4%) and obtains very similar results on the Microscopic one (-0.3%) while using a less complex approach. Table 6: Classification results (accuracy %) on kth-tips-2b using AlexNet and T-CNN-3 separately and combined as well as the state of the art method with a medium depth CNN (VGG-M).…”
Section: Results On Larger Imagesmentioning
confidence: 68%
See 2 more Smart Citations
“…We cannot compare to AlexNet as it requires input images of size 227x227. Our method outperforms the state of the art [8] on the Macroscopic forest species dataset (+1.4%) and obtains very similar results on the Microscopic one (-0.3%) while using a less complex approach. Table 6: Classification results (accuracy %) on kth-tips-2b using AlexNet and T-CNN-3 separately and combined as well as the state of the art method with a medium depth CNN (VGG-M).…”
Section: Results On Larger Imagesmentioning
confidence: 68%
“…More recently, Hafemann [8] applied CNN to a forest species classification, similar to a texture classification problem. While more complex and more accurate than [22], this approach still does not take the characteristics of texture images (statistical properties and repeated patterns) into consideration as it is a simple application of a standard CNN to a texture dataset.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of modelling regression to acquire the best estimation of forest carbon storage would be a new direction, especially (Piao et al 2005a, b) after the breakthrough in the field of deep learning. Some convolutional neural network algorithm (CNN) may have potential for estimating forest carbon stocks combine with remote sensing images, such as Alex (Hafemann et al 2014 (Pietsch and Hasenauer 2002). More than 80% of the forests in China belong to immature forests with young and poor quality secondary forests, which were the main reasons for the low carbon storage and carbon density of forests in China (Liu et al 2000;Zhao and Zhou 2004).…”
Section: Research Trendsmentioning
confidence: 99%
“…Kapp et al [17] assessed multiple feature sets using a quadtree-based approach and reported recognition rates of 95 and 88 % for the microscopic [25] and macroscopic [34] databases, respectively. Hafemann et al [13] took a different approach, and instead of using textural descriptors, they used the images to train a convolutional neural network (CNN). Using the datasets proposed in [25] and [34], they reported accuracies of 95 and 97 %, respectively.…”
Section: Introductionmentioning
confidence: 99%